Mobilization of Criminal Law by Business and State: Socio-Economic Status of Defendants and Pretrial Detention in Economic Cases - Chatsverykova, Iryna (Journal of Economic Sociology, 2018)
Commercialization of law enforcement agencies and the corrupt prosecution of business in Russia could intensify mobilization of criminal law against entrepreneurs, especially when it comes to business conflicts. Mobilization of law starts with calling the police and continues with the following stages of criminal investigation and prosecution. The legal mobilization can be considered successful when the defendant is detained before trial. Using police data on all defendants in Russia charged with economic and corruption crimes from 2013–2014, I examine how the socio-economic status of the defendant and the type of victim are related to pretrial detention decisions. Results indicate that not only the offense but also the defendant’s criminal history, gender, citizenship, and place of residence weigh heavily in investigatory and judicial decision-making on detention in economic and corruption cases. Controlling for major social and legal characteristics, the analysis suggests that entrepreneurs have a similar probability of being detained as governmental officials and that manual workers and have a lower probability than law enforcers and the unemployed. Office workers at commercial companies and state organizations are treated more leniently than entrepreneurs and have the lowest probability of detention. The probability of detention is higher in cases where the victims were citizens or commercial companies (including entrepreneurs), compared to those where defendants damaged the state.